High levels of household food insecurity on the Navajo Nation. Issue 1 (1st February 2013) - Pardilla, Marla; Prasad, Divya; Suratkar, Sonali; Gittelsohn, Joel
Abstract: Objective: To assess levels of and identify factors associated with food insecurity on the Navajo Nation. Design: A cross-sectional study was conducted utilizing the ten-item Radimer/Cornell food insecurity instrument. Sociodemographic, psychosocial and anthropometric data were collected. Setting: Navajo Nation, USA. Subjects: Two hundred and seventy-six members of the Navajo Nation were randomly selected at food stores and other community locations. Results: Of the sample, 76·7 % had some level of food insecurity. Less education (mean years of schooling: P = 0·0001; non-completion of higher education: P = 0·0003), lower full-time employment rates ( P = 0·01), and lower material style of life ( P = 0·0001), food knowledge ( P = 0·001) and healthy eating self-efficacy ( P < 0·0001) scores were all positively associated with food insecurity. Perceived expensiveness ( P < 0·0001) and perceived inconvenience ( P = 0·0001) of healthy choices were also positively associated with food insecurity. Conclusions: Food insecurity rates on the Navajo Nation are the highest reported to date in the USA and are likely attributable to the extremely high rates of poverty and unemployment. Reducing food insecurity on the Navajo Nation will require increasing the availability of affordable healthy foods, addressing poverty and unemployment, and providing nutrition programmes to increase demand.